2021
DOI: 10.3389/fvets.2021.751229
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Staphylococcus aureus From Subclinical Mastitis Cases in Dairy Cows in Rwanda

Abstract: Whole-genome sequencing was carried out on 30 Staphylococcus (S.) aureus isolates from dairy cows with subclinical mastitis from all five provinces of Rwanda. Twenty-five of the isolates produced enough sequence to be analyzed using core genome multilocus sequence typing (cg-MLST). The isolates group into three main clusters. The largest cluster contain isolates of sequence type (ST) 152 (n = 6) and the closely related ST1633 (n = 2). These sequence types have previously mainly been encountered in humans. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Bovine isolates were frequently ST97 and ST151, while most ST8, ST59, ST152, ST239 were from human sources. That said, these sequence types have been associated with both hosts consistent with zoonotic transmission in previous studies (Ndahetuye et al, 2021). The ST59, ST239, ST5, ST228, ST630, ST30, ST80, ST45 and ST88 were often from human cases in the current study.…”
Section: Gene Profiles Mlstsupporting
confidence: 89%
“…Bovine isolates were frequently ST97 and ST151, while most ST8, ST59, ST152, ST239 were from human sources. That said, these sequence types have been associated with both hosts consistent with zoonotic transmission in previous studies (Ndahetuye et al, 2021). The ST59, ST239, ST5, ST228, ST630, ST30, ST80, ST45 and ST88 were often from human cases in the current study.…”
Section: Gene Profiles Mlstsupporting
confidence: 89%
“…To cater for the high demand for milk and red meat in Dar es Salaam, a large influx of cattle from different parts of the country may Five resistant conferring genes were predominantly observed in the dataset. blaZ, the gene conferring for penicillin resistance, was prevalent, at 84%, which is a common occurrence among bovine S. aureus as the antibiotic is frequently used to treat intramammary infections in cattle [12,33]. The streptomycin-resistant gene str was only detected in bovine S. aureus and tetK, in which it was prevalent at 23% and 24%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus is a public health problem worldwide and an important opportunistic pathogen in both humans and animals ( 1 ). S. aureus is common in mastitis cases in East African countries ( 2 ). Most of the reported S. aureus strains in Africa were novel, belonging to CC97 ( 3 , 4 ).…”
Section: Announcementmentioning
confidence: 99%
“…Most of the reported S. aureus strains in Africa were novel, belonging to CC97 ( 3 , 4 ). More recent studies have reported that ST5477 is one of the major ST types as bovine adapted S. aureus and causes mastitis, with a number of sequenced strains ( 2 , 5 ). Nonetheless, none of them has been made as a complete genome.…”
Section: Announcementmentioning
confidence: 99%